Plasma 25-OH vitamin D3 level in HIV infected patients - Deveci, Aydın; Bilgici, Birsen (Progress in Nutrition, 2021)
Vitamin D is an important modulator of calcium metabolism and bone mineral density. In addition, it has effect on various organ systems including immunologic, cardiovascular and central nervous systems. We aimed to determined plasma 25-OH Vit D3 for evaluation of vitamin D status among HIV infected patients. Medical records of patients infected with HIV were searched retrospectively. One hundred twenty patients infected with HIV who plasma 25-OH Vit D3 level was determined by liquid chromatography tandem mass spectrophotometer enrolled into the study. Plasma 25-OH Vit D3 levels of the patients ranged between 4.26 and 68.57 µg/L (mean: 21.71±13.08 µg/L). Normal plasma level (>30 µg/L) was determined only in 26 (21.6%) patients. Female patients had lower plasma level (11.29±4.53 vs 24.19±13.24 µg/L). It was not determined correlation between CD4 count and plasma 25-OH Vit D3 level (r:-0.04) There was negative moderate correlation between age and plasma 25-OH Vit D3 level (r:-0.42). In conclusion, most of patients (78.3%) had low level 25-OH Vit D3. Therefore, it is important to determine vitamin D status of patients and give replacement therapy when required during following HIV infected patients.